Chapter 2 Trouble with "Status" Competing Models of British and North American Public Health Nursing Education and Practice in British Malaya - Wall, Rosemary (National University of Singapore Press, 2017)
This chapter has explored the role of training and education as a light- ning rod for rival models and interpretations of public health nursing. Nurses faced the constraints of conventional British social norms of class and gender in Malaya, contrasted with respect, status, and opportunities from North Americans. Hostility was displayed towards Americans within the Malayan medical services, affecting the way in which the RF-trained British nurses perceived colonial society, following their interaction with their friendlier and more egalitarian cross-Atlantic colleagues. The chapter also reveals how British, American, and international organizations' efforts and funding to improve public health nursing in rural areas coincided with periods of increased nationalism in the 1920s and communism in the late 1940s and early 1950s. In the 1920s, in particular, the RF, rather than the British, drove public health nursing in Malaya, enhancing health care in politically fragile rural areas.